Volterra Integral Equation and Logistic Drop-Offloading for Collaborative Mobile Fog Crowd Sensing - P. Ananthi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Volterra integral and logistic drop-offloading are two methods that can be used for crowd sensing in a collaborative mobile fog environment. Volterra integral allows for detecting a target object in a scene, while logistic drop-offloading can be used to determine the target object's position. These methods can be used together to improve the accuracy of crowd sensing in a collaborative mobile fog environment. This method utilizes the Volterra integral to approximate the crowd sensing function and then uses the logistic function to drop off the data sensed by the crowd. This method is shown to be effective in reducing the error in the crowd-sensing function. It is also shown to be more efficient regarding computational time and energy consumption.